Percutaneous Coronary Intervention for Iatrogenic Right Coronary Artery Dissection Post Bentall Procedure: A Case Report and Minireview - Sameer Saleem; Mubbasher A. Syed; Khalid Changal; Abdulelah Nuqali; Mujeeb Sheikh (Case Reports in Cardiology)
Iatrogenic coronary artery dissection is a potentially life-threatening complication of cardiovascular interventions. The optimal management of iatrogenic coronary artery dissection is not clear; however, both conservative management and percutaneous or surgical revascularization have been performed depending on the patient’s clinical status and the extent of dissection. We present the first reported case of right coronary artery dissection after Bentall procedure performed for ascending aortic aneurysm. Urgent percutaneous intervention using adjunctive coronary imaging was performed with excellent clinical recovery. In this article, we highlight coronary artery dissection after Bentall procedure as a possible complication, provide an insight into various options in its management, and review published data on iatrogenic coronary artery dissection. We also discuss the challenges in percutaneous treatment of coronary artery dissection with special focus on intracoronary imaging for accurate diagnosis and guidance in the management of this complex lesion.